Populasi dan Biomassa Cacing Tanah Akibat Aplikasi Biochar dan Kotoran Ayam di Tanah Ultisol pada Pertanaman Jagung (Zea mays L.) Musim Tanam Ke-3 - Arjuana, Danang; Arif, M.A. Syamsul; Prasetyo, Dedy; Dermiyati, Dermiyati; Septiana, Liska Mutiara; Lumbanraja, Jamalam (JURNAL AGROTROPIKA, 2024)
Ultisols have problems with soil organic matter and low nutrients, that making soil fertility low. Population and earthworm biomass is one indicator of the fertility level of a soil. Efforts to increase soil fertility can be done by giving biochar and chicken manure. This study aims to study the effect of biochar and chicken manure application on earthworm population and biomass and study the correlation between earthworm population and biomass with soil properties. This research uses a non-factorial Group Randomized Design (RAK) with 4 groups and 4 treatments, namely, B0 = control, B1 = biochar 5 tons ha-1, B2 = chicken manure 5 tons ha-1, and B3 = biochar 5 tons ha-1 + chicken manure 5 tons ha-1. The data was analyzed for variance, followed by a 5% BNT test, as well as a correlation test between earthworm population and biomass with supporting variables. The results showed that the application of biochar and chicken manure had no effect on earthworm population and biomass at the entire time of observation. There is a negative correlation between soil water content with earthworm populations and soil temperature with earthworm biomass. There is a positive correlation between soil pH with earthworm populations and biomass, but there is no correlation between earthworm populations and biomass with corn crop production components. Two families of earthworms found in the research area are Megascolecidae and Glossoscolecidae. Key words: Glossoscolecidae, Megascolecidae, soil ameliorant, Ultisol